Pengaruh Total Asset Turnover (TAT), Kualitas Aktiva Produktif (KAP) terhadap Profitabilitas (ROA) dengan Non Performing Financing (NPF) sebagai Variabel Moderasi pada Bank Umum Syariah di Indonesia Periode 2018-2022 - Pardede, Diah Hafni; Nawawi, Zuhrinal M.; Atika, Atika (FAKULTAS EKONOMI DAN BISNIS ISLAM, 2023)
This study aims to find out how the influence of Total Asset Turnover (TAT), Earning Asset Quality (KAP) on Profitability (ROA) with Non Performing Financing (NPF) as Moderating Variables in Islamic Commercial Banks in Indonesia Period 2018 - 2022. The independent variables used are TAT and KAP, the dependent variable used in this study is Profitability (ROA) and the moderating variable is NPF. The research data used is secondary data, TAT level, KAP level and also the level of profitability (ROA) and obtained from the official website of each Islamic Commercial Bank in Indonesia which has been published in the Financial Services Authority (OJK). The research data consists of 30 data where the data used is annual data. The research method used in this research is quantitative with a descriptive approach. The analysis technique used in this study is a partial test (t test), simultaneous test (F test), coefficient of determination test (R2) and MRA analysis test using the SPSS Version 25.00 analysis tool. The results showed that the TAT variable had no significant positive effect on ROA. KAP variable has a significant positive effect on ROA. KAP and TAT variables simultaneously influence ROA. The NPF variable is not able to moderate the effect of TAT on ROA. The NPF variable is not able to moderate the effect of KAP on ROA. So the KAP variables and NPF variables were not able to strengthen and give a significant effect on ROA partially in this study.